2011
DOI: 10.3109/01443615.2011.623806
|View full text |Cite
|
Sign up to set email alerts
|

Training obstetricians and gynaecologists to be emotionally intelligent

Abstract: The concept of emotional intelligence (EI), a model that encompasses all of the skills in the patient-doctor relationship, has been applied to medical education in recent years. Doctors in obstetrics and gynaecology (O&G) often deal with emotionally demanding situations for themselves and for their patients, and therefore, EI skills may be vital and should be part of any training curriculum. Using novel methodology, 16 O&G consultants from across the North-West of England were asked to investigate (using a cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Multiple authors have suggested educational training as a way to improve EI (Berman and West, 2008;Gignac et al, 2012;Laabs, 1999;Oginska-Bulik, 2005;Ornstein and Nelson, 2006;Pilkington et al, 2012;Slaski and Cartwright, 2003;Zijlmans et al, 2011) and empirical data suggest that training can effectively increase EI (Gignac et al, 2012;Herpertz et al, 2016;Khodayarifard et al, 2012;Slaski and Cartwright, 2003;Zijlmans et al, 2011). One study found evidence to support increases in emotional identification and emotion management abilities among individuals who were trained in EI (Nelis et al, 2009).…”
Section: Emotional Intelligence Development and Nursingmentioning
confidence: 99%
“…Multiple authors have suggested educational training as a way to improve EI (Berman and West, 2008;Gignac et al, 2012;Laabs, 1999;Oginska-Bulik, 2005;Ornstein and Nelson, 2006;Pilkington et al, 2012;Slaski and Cartwright, 2003;Zijlmans et al, 2011) and empirical data suggest that training can effectively increase EI (Gignac et al, 2012;Herpertz et al, 2016;Khodayarifard et al, 2012;Slaski and Cartwright, 2003;Zijlmans et al, 2011). One study found evidence to support increases in emotional identification and emotion management abilities among individuals who were trained in EI (Nelis et al, 2009).…”
Section: Emotional Intelligence Development and Nursingmentioning
confidence: 99%
“…Both emotional intelligence and cultural intelligence have been popular topics for researchers. Many organizations have undertaken programs to train individuals in emotional intelligence (Byron Stock & Associates, 2008; Hays, 1999; Pilkington et al, 2012; Zijlmans et al, 2011) or participated in studies related to training emotional intelligence (Gignac et al, 2012; Slaski and Cartwright, 2003). Training aspects of cultural intelligence has also occurred in organizations (Bean, 2006; MacNab et al, 2012; Young, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A physician with good know how of his emotional competencies could fulfill the demands of the patients better (Goldzweig et al, 2015). Andrea Pilkington et al stated that emotional intelligence is highly related to patient satisfaction level and improvement in the score of EI simultaneously enhance patient satisfaction and decrease litigation in obstetrics and gynecology (Pilkington et al, 2012). High EI is associated with high patient satisfaction with low litigation against the doctors and vice versa (Shouhed et al, 2019).…”
Section: Figurementioning
confidence: 99%
“…This is similar to the results seen for patient satisfaction in our study. Improvement in EI of residents of gynecology by focused interventions could reduce complaints in this specialty (Pilkington et al, 2012).…”
Section: Figurementioning
confidence: 99%